2016
DOI: 10.1016/j.celrep.2016.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Role for the IFT-A Complex in Selective Transport to the Primary Cilium

Abstract: Summary Intraflagellar transport sub-complex A (IFT-A) is known to regulate retrograde IFT in the cilium. To rigorously assess its other possible roles, we knocked out an IFT-A subunit, IFT121/WDR35, in mammalian cells and screened the localization of more than 50 proteins. We found that Wdr35 regulates cilium assembly by selectively regulating transport of distinct cargoes. Beyond its role in retrograde transport, we show that Wdr35 functions in fusion of Rab8 vesicles at the nascent cilium, protein exit from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
85
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(100 citation statements)
references
References 64 publications
15
85
0
Order By: Relevance
“…These correlations suggest that the different phenotypes might reflect differences in cilia assembly and function. In addition, a recent study showed selective cargo transport activity of WDR35 in regulating cilium assembly in human RPE1 cells (Fu et al, ). Further investigation of IFT particles and specific cargos would provide deeper insight into the mechanisms that dictate the effects on skeletogenesis among the skeletal ciliopathies.…”
Section: Discussionmentioning
confidence: 99%
“…These correlations suggest that the different phenotypes might reflect differences in cilia assembly and function. In addition, a recent study showed selective cargo transport activity of WDR35 in regulating cilium assembly in human RPE1 cells (Fu et al, ). Further investigation of IFT particles and specific cargos would provide deeper insight into the mechanisms that dictate the effects on skeletogenesis among the skeletal ciliopathies.…”
Section: Discussionmentioning
confidence: 99%
“…Through a study of a series of truncating mutations, the minimal IFT121 regions required for binding to other complex components were determined [38]. Based on these data, the SRPS missense mutations identified here are predicted to interfere with IFT121 binding to core complex member IFT122 and the centrosomal protein 290-KD (Cep290).…”
Section: Discussionmentioning
confidence: 99%
“…WDR35 is also known as IFT121, a component of IFT‐A found in primary cilia (Behal et al, ; Blacque et al, ), where it plays roles in formation and is required for retrograde intraflagellar transport (Fu et al, ). Primary cilia formation is required for nutrient sensing and signal transduction induced by autophagy, which is negatively regulated by mTORC1 (Parmigiani et al, ; Tang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…WDR35 has been implicated in multiple genetic diseases, including Sensenbrenner syndrome (Bacino, Dhar, Brunetti-Pierri, Lee, & Bonnen, 2012;Gilissen et al, 2010;Hoffer, Fryssira, Konstantinidou, Ropers, & Tzschach, 2013), short rib polydactyly syndromes (Mill et al, 2011) and Ellis-van Creveld syndrome (Caparros-Martin, Luca, & Cartault, 2015), which indicates that it plays important roles in development, although how it influences development has not been elucidated. In addition, the intraflagellar transport (IFT)-A complex containing WDR35 is involved in selective transport in primary cilia (Fu, Wang, Kim, Li, & Dynlacht, 2016). WDR35 expression is regulated through mechanisms, including AMPK, ROS and p38 MAPK phosphorylation (Tsunekawa et al, 2013).…”
mentioning
confidence: 99%